Influência da concentração de H2O2 na síntese de Nb2O5 com atividade fotocatalítica sob luz visível - Silva, Roberta Resende Maciel da (2019)
Heterogeneous photocatalysis is a technology that can be used for the treatment of wastewater and one of the interesting aspects of this technique is the possibility of using visible light (solar) to activate the photocatalyst. However, the photocatalytic properties of the materials typically used in this process still need to be optimized so that they can be sensitive to this type of radiation. To overcome this limitation, this work describes a new and versatile method to obtain visible-light-harvesting photocatalysts based on the peroxo-niobium oxide synthetized by the oxidant peroxo method (OPM) and crystallized under hydrothermal conditions in a one-step approach. The ability of Nb2O5 to form reactive oxygen species (peroxo and superoxo) using the OPM method was investigated in respect to the Nb/H2O2 molar ratio (1:2, 1:5, 1:10 and 1:12) in the synthesis medium. The structural and surface properties of the synthesized materials were characterized by XRD, Raman spectroscopy, TEM, N2 adsorption, FTIR, XPS and UV-Vis DRS. The photocatalytic activity was evaluated by monitoring the oxidation of caffeic acid, a toxic and recalcitrant phenolic compound present in the effluents of winemaking and coffee processing. The results revealed an increase in the photoactivity of the materials when using Nb/H2O2 molar ratios greater than 1:2 due to the higher amount of reactive oxygen species formed on the niobia surface, suggesting that the peroxo groups allowed the activation of the photocatalyst under visible light and superoxo anions contributed to increase the photocatalytic efficiency. In addition to the hydrogen peroxide content, the autogenous pressure developed during the hydrothermal reaction was essential for the formation of these species, since the increase of the H2O2 concentration in the synthesis medium caused a significant increase of the autogenous pressure.